THE INFLUENCE OF COMPETENCE, COMMUNICATION, AND PROFESSIONALISM ON EMPLOYEE SATISFACTION AT UD. SAMI ASRI TULUNGAGUNG: Pengaruh Kompetensi, Komunikasi, dan Profesionalisme terhadap Kepuasan Karyawan di UD. Sami Asri Tulungagung - Abie Nur Budi Pangestiko; Indah Yuni Astuti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Employee satisfaction is one of the indicators of organizational performance that reflects the quality of human resource management. This study aims to analyze the influence of competence, communication, and professionalism on employee satisfaction at UD Sami Asri Tulungagung, a producer of Tulungagung’s signature rambak crackers. The study used a quantitative approach with an associative design. The study population included all 35 employees, and data collection was conducted through a questionnaire with a Likert scale of 1–5 and short interviews. The research variables included competence, communication, professionalism as independent variables, and employee satisfaction as the dependent variable. Data analysis was conducted using descriptive statistics, simple regression, and multiple regression using SPSS version 25. The results showed that competence, communication, and professionalism each had a positive and significant influence on employee satisfaction. Professionalism was the dominant variable that provided the highest contribution to employee satisfaction. Simultaneous analysis showed that the three independent variables together explained 67.1 percent of the variation in employee satisfaction. These findings indicate that increasing employee satisfaction at UD Sami Asri can be achieved through competency development, effective communication, and consistent application of professionalism. This research provides implications for human resource management in small and medium enterprises in order to create a conducive, productive work environment that is able to increase employee loyalty.